Analyzing the effects of financial and housing wealth on consumption using micro data - Cáceres, Carlos (IMF working paper ;, 2019)
This paper analyzes the existence of 'wealth effects' derived from net equity (in the form of housing, financial assets, and total net worth) on consumption. The study uses longitudinal household-level data?from the Panel Study of Income Dynamics (PSID)?covering about 7,000-9,000 households in the U.S., with the estimations carried over the period 1999-2017. Overall, wealth effects are found to be relatively large and significant for housing wealth, but less so for other types of wealth, including stocks. Furthermore, the analysis shows how these estimated marginal propensities to consume (MPC) from wealth are closely linked to household characteristics, including income and demographic factors. Finally, underlying structural changes in household characteristics point to potentially lower aggregate MPCs from wealth going forward.